2022
DOI: 10.1155/2022/9479755
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Construction of College English Teaching Environment Assessment Model Based on BP Neural Network and Multiple Intelligence Theory

Abstract: College English has almost always been a required course, and a college student’s level of English proficiency is one of the factors used to assess their learning capacity. The quality of students’ English learning is largely influenced by the level of English instruction provided in colleges. However, there are still a lot of issues with college English instruction today, the most glaring of which is that English instruction is being overly simplified, and that the methods, modes, and purposes of instruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Wilson (2018)adds that learners' varied intelligences should be manifested in their learning processes, outcomes, and thinking, rather than merely tests and examinations. According to Hailong (2022), there is a need to the MIT to establish a multi-assessment system for college English teaching and learning with the aim of offering an effective and workable solution to several issues in the language classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson (2018)adds that learners' varied intelligences should be manifested in their learning processes, outcomes, and thinking, rather than merely tests and examinations. According to Hailong (2022), there is a need to the MIT to establish a multi-assessment system for college English teaching and learning with the aim of offering an effective and workable solution to several issues in the language classroom.…”
Section: Discussionmentioning
confidence: 99%
“…By understanding these factors, teachers can tailor their lesson plans and teaching strategies to address specific learning objectives and ensure that each student receives personalized support [11]. Furthermore, optimization in English teaching involves the strategic selection and integration of instructional resources and materials [12]. This might include incorporating multimedia tools, educational software, authentic texts, and interactive activities that cater to diverse learning styles and enhance student engagement.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%